Isolation and identification of an antibacterial compound in sea grapes (Caulerpa chemnitzia (Esper) J.V. Lamouroux) - Latona, Charmelie G.; Veronica Julia G.; Toralba, Joanna V. (Manila Department of Pharmaceutical chemistry, College of Pharmacy, University of the Philippines Manila, 2025)
Antibiotics kill or inhibit bacterial growth that causes infectious diseases, drastically changing modern medicine. Unfortunately, the increasing trend in bacterial drug resistance and the decreasing trend in the discovery of antibiotics prompt researchers to find alternative sources of novel secondary metabolites. While most bioactive compounds originate from terrestrial sources, the vast marine ecosystem remains largely unexplored. As a marine biodiversity hub, the Philippines houses a variety of marine organisms such as seaweeds and sea grapes. Caulerpa chemnitzia, one of the green seaweeds of the Caulerpa species wildly abundant in La Union, was reported to have potential antibacterial activity. The study aimed to identify the antibacterial compound/s in C. chemnitzia against Staphylococcus aureus subsp. aureus ATCC 29213.

The crude ethanolic extract of C. chemnitzia was subjected to liquid-liquid partitioning. The ethyl acetate layer was fractionated using open-column chromatography using n-hexane:acetone (80:20). The two major pooled fractions were further purified through another column using toluene:ethyl acetate (80:20). The resulting fractions were subjected to Thin-layer chromatography-Contact Bioautography (TLC-CB) to assess the antibacterial activity against S. aureus. The results showed white clearing zones against a purple background in areas corresponding to active compounds, confirming antibacterial activity. Compounds with antibacterial activity were found to be colorless under white light, non-quenching under 254 nm UV, and non-fluorescent under 366 nm UV, produced blue/violet spots when sprayed with vanillin-H2SO4 spray and showed inhibition zones after MTT staining.

The liquid chromatography–time-of-flight mass spectrometry (LC-ToF/MS) allowed for the putative identification of secondary metabolites through database matching with a Personal Compound Database and Library (PCDL). Among the six compounds putatively identified via LC-ToF/MS, four were found to have potential antibacterial activity: cacospongionolide C, alpha-tocospirone, alpha-tocospiro A, and/or (23E)-3β-Hydroxystigmasta-5,23-dien-28-one. The first compound was successfully isolated from the fractions and confirmed to be associated with a bioactive spot on the TLC plate, providing direct evidence of antibacterial potential. Based on the current available literature, this might be the first report on the antimicrobial activity of these secondary metabolites.

At large, the results provide information that marine algae such as Caulerpa chemnitzia are great sources of novel bioactive compounds. The integration of chromatography, bioautography, and LC-ToF/MS analysis proved effective in identifying compounds with antibacterial activity from marine natural products.
Keywords: Caulerpa chemnitzia -- Phytochemistry -- Antibacterial activity; Marine algae -- Antibacterial agents -- Natural product drug discovery; Bioactive compounds -- Isolation and identification -- Seaweeds; Antibacterial activity; Caulerpa; Caulerpa chemnitzia; Contact Bioautography; TLC